2001
DOI: 10.1053/rmed.2000.0970
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte markers in induced sputum in patients with respiratory disorders and healthy persons obtained by two sputum-processing methods

Abstract: Induced sputum is increasingly used to detect and monitor airway inflammation in respiratory diseases. However, the processing of sputum has been rather laborious for clinical practice. The aim of this study was to improve the practicality of induced-sputum studies by simplifying sample processing. Eosinophil cationic protein (ECP), eosinophil peroxidase (EPO), neutrophil lipocalin (HNL) and myeloperoxidase (MPO) were used as biochemical markers of airway inflammation and the results of the study method were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 31 publications
4
43
0
1
Order By: Relevance
“…This inflammation may respond poorly to conventional treatments [21] (I. Helenius, Helsinki University Central Hospital, unpublished results), but appears to be partly reversible after stopping intensive training [20]. The sputum differential cell count of the athletes is also very similar to that observed in patients with lower respiratory tract infection [22].…”
Section: Validity Of the Datamentioning
confidence: 74%
“…This inflammation may respond poorly to conventional treatments [21] (I. Helenius, Helsinki University Central Hospital, unpublished results), but appears to be partly reversible after stopping intensive training [20]. The sputum differential cell count of the athletes is also very similar to that observed in patients with lower respiratory tract infection [22].…”
Section: Validity Of the Datamentioning
confidence: 74%
“…Although, the levels of iNOS have been found to be elevated in the induced sputum of asthmatics (Sugiura et al 2003), variable levels of iNOS have been reported in COPD patients (Ichinose et al 2000;Rytila et al 2006). EPO is elevated in asthma while MPO, which is expressed in neutrophils and monocytes (Kim et al 2001), is elevated in COPD with the levels being higher in COPD than in asthma (Metso et al 2001). A rather similar elevation in the number of MPO-positive cells is seen in the induced sputum of chronic nonsymptomatic smokers and chronic symptomatic smokers with normal lung function, who are considered to be at risk of developing COPD .…”
Section: Oxidant-generating Enzymesmentioning
confidence: 99%
“…Flow-volume curves were generated, FeNO and airway hyperresponsiveness to acetylcholine were measured, and sputum was induced and processed in accordance with previously reported procedures [7,8,10,11].…”
Section: Other Examinationsmentioning
confidence: 99%